MANFAAT IKAN TERI SEGAR (Stolephorus sp) TERHADAP PERTUMBUHAN TULANG DAN GIGI - Endah Aryati E; Agustin Wulan Suci Dharmayanti (Odonto : Dental Journal, 2014)
Background: Nutrition and diet intake are such related with growth and development of body organs, including growth and development of bone and teeth. High quality and concentration of protein and cancium in food have linier relationship with growth and development of bone and teeth. Anchovies are high quality protein and calcium source. Anchovies are cheap calcium and protein source that can be available in Indonesia. This review was aimed to review the benefits of anchovies to development of bone and teeth. Discussion : DisAnchovies are high quality food because all of the body can be consumed. Bone of anchovies contains protein and calcium. Per 100 gram of anchovies contain 77 kcal of energy; l6 gr protein; 1.0 gr fat; 500 mg calcium; 500 mg phosfor; 1.0 mg ferrum; 47 Vit A; and 0.1 mg Vit B. Protein and calcium were needed by body fore repairing process and structed the tissue. Protein was as bone matrix. Calcium of anchovies was good for bone, teeth and had calming effect. Moreover, vitamin A of anchovies was also important for bone and teeth development. Conclusion: anchovies could be used as essential nutrition to optimal of bone and teeth development.